Funding of Scientific Research at the Universities of Medical Sciences of Cuba. Realities, Challenges and Legal Aspects. - Mikhail Benet Rodríguez; Lázaro López Torres; Rafael Leiva Rangel; Esther Hernández Pérez; Yusimy Miranda Pérez; Beatriz García Alpizar (Medisur, 2011)
Funding of scientific activity is essential for its development and in turn, for contributing to national development. There are many problems in both planning and executing that budget in the medical universities in Cuba, a situation that is similar in the rest of the centers of the National Health System. This paper draws attention to this issue and also presents a summary of the laws and resolutions in the country that allow proper planning and implementation of the budget to achieve scientific development. The legal issues should be responsibly considered by both researchers and decision-makers of the system.